2012
DOI: 10.1136/archdischild-2012-302724.1512
|View full text |Cite
|
Sign up to set email alerts
|

1512 Validity of the Clinical Neurological State in Diagnosing Diabetic Peripheral Neuropathy

Abstract: Pearson-Chi Square revealed a significant relationship between abnormal EEG and the development of further seizures (p<0.01). The odds of having further seizures if the EEG was abnormal was 4.9 (95% C.I 1.5-16.1). Conclusions Sleep EEG is a useful tool in predicting the risk of developing epilepsy in children with first afebrile seizure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Meh and Denislic found that the subclinical involvement of peripheral nervous system in diabetic children is 87%. 10 Subclinical abnormalities in cardiovascular and gastrointestinal autonomic function may be found at diagnosis or even in teenage diabetic patients. 11,12…”
Section: Definitionmentioning
confidence: 99%
“…Meh and Denislic found that the subclinical involvement of peripheral nervous system in diabetic children is 87%. 10 Subclinical abnormalities in cardiovascular and gastrointestinal autonomic function may be found at diagnosis or even in teenage diabetic patients. 11,12…”
Section: Definitionmentioning
confidence: 99%